2012
DOI: 10.1111/j.1574-6941.2012.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of methane in hypersaline cold seep sediments

Abstract: Life in hypersaline environments is typically limited by bioenergetic constraints. Microbial activity at the thermodynamic edge, such as the anaerobic oxidation of methane (AOM) coupled to sulphate reduction (SR), is thus unlikely to thrive in these environments. In this study, carbon and sulphur cycling was investigated in the extremely hypersaline cold seep sediments of Mercator mud volcano. AOM activity was partially inhibited but still present at salinity levels of 292 g L(-1) (c. eightfold sea water conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 97 publications
7
40
1
Order By: Relevance
“…Combined with geochemical data, these results confirmed that ANME-1 preferred completely anoxic and highly sulfidic sediments and suggested that ANME-1 ecophysiology could depend on environmental conditions and more particularly on sulfate concentrations. In sulfate-poor and methanerich EWM14 sediments, ANME-1 could support a bacterial-independent AOM as suggested previously (Orphan et al, 2002;Maignien et al, 2012), using a different metabolic pathway providing terminal electron acceptors for AOM, such as the use of extracellular proteins, as mentioned by recent metaproteomic analyses (Stokke et al, 2012). Such metabolism, independent of bacterial association and then metabolic bacterial requirements, could occur and be more competitive than syntrophic AOM in EWM14 sediments.…”
Section: Discussionsupporting
confidence: 52%
“…Combined with geochemical data, these results confirmed that ANME-1 preferred completely anoxic and highly sulfidic sediments and suggested that ANME-1 ecophysiology could depend on environmental conditions and more particularly on sulfate concentrations. In sulfate-poor and methanerich EWM14 sediments, ANME-1 could support a bacterial-independent AOM as suggested previously (Orphan et al, 2002;Maignien et al, 2012), using a different metabolic pathway providing terminal electron acceptors for AOM, such as the use of extracellular proteins, as mentioned by recent metaproteomic analyses (Stokke et al, 2012). Such metabolism, independent of bacterial association and then metabolic bacterial requirements, could occur and be more competitive than syntrophic AOM in EWM14 sediments.…”
Section: Discussionsupporting
confidence: 52%
“…Although no sequences affiliating with the candidate division MSBL--1 (originally described from anoxic DHAB brines and thought to have a methanogenic metabolism; van der Wielen et al 2005) were detected, the archaeal OTUs we detected in our cDNA libraries are believed to have a putative methanogenic metabolism based on their phylogeny (van der Wielen et al 2005). Representatives of the archaeal ANME--1 group have also been suggested to be halotolerant as they have been found in high--salt concentration environments (Lloyd et al 2006;Maignien et al 2013;Pachiadaki et al 2014). Our results indicate that there may be additional important archaeal taxa involved in DHAB methane cycling aside from MBSL--1, and possibly ANME--1.…”
Section: Methodsmentioning
confidence: 78%
“…Although ANME-1 archaea have been found most frequently in sulfate-depleted environments (Yanagawa et al, 2011), they are known to be adapted to hypersalinity (Lloyd et al, 2006;Maignien et al, 2013). This suggests salinity is a stronger selective force for this group than sulfate concentration.…”
Section: Methanogenesis and Aommentioning
confidence: 98%